Influence of self - concealed psycho - social factors as predictors on the effectiveness of sexual self - disclosure during voluntary counseling and testing among university students in Kenya - Maroko, Mokua Gilbert; Ogola, Fredrick; Kithuka, Musau; Gatumu, Haniel Nyaga; Gathoni, Nyutu Jane; Nyamugoro, Njuguna Christina; Ireri, Anthony Muriithi (International Journal of Psychology and Counselling, 2015)
Four hundred and fifty six third year undergraduate students from the University of Nairobi, Kenyatta University and Egerton University were studied to find out the influence of self-concealed psycho-social factors as predictors on the effectiveness of sexual self-disclosure during voluntary counselling and testing among university students in Kenya. Results revealed there is a significant relationship between self-concealed psycho-social factors and sexual self-disclosure. Students’ marital status, relational mobility and cues that relate to privacy were found to be the best predictors of sexual self-disclosure by determining details of how much sexual information they disclosed during voluntary counselling and testing. Implications of these findings and recommendations for further research are discussed
Keywords: Self - concealed; Psycho - social factors; Sexual self - disclosure